Inequalities on Generalized Sasakian Space Forms - Najma Abdul Rehman; Abdul Ghaffar; Esmaeil Abedi; Mustafa Inc; Mohammed K. A. Kaabar (Journal of Function Spaces)
In this paper, we find the second variational formula for a generalized Sasakian space form admitting a semisymmetric metric connection. Inequalities regarding the stability criteria of a compact generalized Sasakian space form admitting a semisymmetric metric connection are established.